Sustainability disclosure as a mechanism for improving financial performance of manufacturing companies in Nigeria - Adedeji Gbadebo (New Applied Studies in Management, Economics & Accounting)
The persistent increases in carbon emissions, air pollution, noise pollution, socio economic issues, and other environmental hazards have adverse effects on the performance of global companies. The non-disclosure of this information in the annual report has caused investors and other stakeholders to lose confidence. This study investigates how carbon disclosure has affected the financial performance of manufacturing companies in Nigeria. The paper examined the case of five companies consistently listed on the Nigeria Exchange Group from 2014 to 2023. Sustainability disclosure was captured using carbon productivity and environmental expenditure disclosure measures, while financial performance was proxied by return on asset. The result shows that environmental expenditure and carbon productivity increase financial performance, but the increase was not significant. Likewise, social innovation investment controlled for has a positive but insignificant influence on the financial performance of the firms. A similar outcome is evident for the return on equity when applied as the measure of financial performance, suggests that the estimation is not sensitive to the measure of financial performance applied. The outcomes offer implications for regulations, policy making and investment decisions in the capital market. The paper recommends that regulatory agencies in Nigeria, including the Financial Reporting Council of Nigeria and other relevant bodies should continue monitoring companies, particularly manufacturing firms, to disclose their negative and positive impacts.